TEACHING WRITING TO EFL UNIVERSITY STUDENTS: SOME IMPORTANT ISSUES : (Reducing Writer’s block and Breakthrough to Better Teaching) - Hijjatul Qamariah (Getsempena English Education Journal, 2016)
This article discussed that the students’ difficulties in writing can be triggered by a lot of factors, but to solve those difficulties is never ending story. While correction of piece of writing is believed can helped students improve their writing, but the fact that the implementation of correction still cannot solve the problem. Moreover, students tend to be apprehensive. Writing apprehensive is dealing with the anxiety about writing. Students feel fear when they are assigned to write a piece of writing. This nevertheless, is a problematical issue that needs to be solved by the writing instructor or teacher. Some experts stated that writing apprehension can be caused by several factors, such as lack of writing strategies, inappropriate teachers’ writing teaching techniques, inappropriate contain of writing textbooks, and the students’ cognitive. Therefore, a better teaching instruction perhaps will minimize students’ apprehension in writing. This article tries to give an insight for a better teaching writing and how to deal with the problem that the students face when writing.